Syphilis Masquerading As Mass Lesions: The Utility of Modern-Day Imaging and Molecular Sequencing in Clinical Diagnosis. Issue 5 (May 2017) - Lin, Ray Junhao; Choudhury, Saugata; Lee, Cheng Chuan; Lee, Tau Hong
Abstract : Abstract: Syphilis has been known to present in a myriad of symptoms throughout the ages, and until this day, the diagnosis remains elusive to the modern physician. We present 2 unusual cases of syphilis that posed diagnostic challenges even in the current era of new and advancing diagnostic tests. Abstract : We report 2 cases of syphilis in patients with human immunodeficiency virus infection that presented as tumor-like lesions. 16S ribosomal RNA sequencing was performed to facilitate the diagnosis.